2021
DOI: 10.1002/ejlt.202000369
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, In Vivo and In Vitro Evaluation, and Pharmacodynamic Study of DMY‐Loaded Self‐Microemulsifying Drug Delivery System

Abstract: Hyperlipidemia has become a common disease in modern society with its prevalence becoming relatively high in the world. A series of complications that accompany hyperlipidemia are seriously threatening individuals’ health. Dihydromyricetin (DMY) is a kind of polyphenol hydroxy (OH) dihydroflavonol extracted from the stems and leaves of Ampelopsis grossedentata. It has a variety of pharmacological activities. This study aims to develop a self‐microemulsifying drug delivery system (SMEDDS) to improve the oral bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…For the oral/enteral route, a study by Liu et al 31) showed that MCTs (RH40) produced a ZP value of −25 mV indicating a good colloidal stability. Another study by Luo et al 30) showed that the MCTs exhibited a ZP of −44.4 mV leading to an excellent stability, while those in a study by Wang et al 34) showed a ZP value of 17.37 mV. For the parenteral route, the MCTs in a research by Khan et al 40) showed a ZP of −22±1.5 mV leading to a moderate stability.…”
Section: The Effect Of Mcts On Ddsmentioning
confidence: 96%
See 3 more Smart Citations
“…For the oral/enteral route, a study by Liu et al 31) showed that MCTs (RH40) produced a ZP value of −25 mV indicating a good colloidal stability. Another study by Luo et al 30) showed that the MCTs exhibited a ZP of −44.4 mV leading to an excellent stability, while those in a study by Wang et al 34) showed a ZP value of 17.37 mV. For the parenteral route, the MCTs in a research by Khan et al 40) showed a ZP of −22±1.5 mV leading to a moderate stability.…”
Section: The Effect Of Mcts On Ddsmentioning
confidence: 96%
“…Another study by Wang et al 34) proposed the development of a self-microemulsifying drug delivery system (SMEDDS) to evaluate the oral bioavailability and hypolipidemic activity of dihydromyricetin (DMY) . The SMEDDS was composed of a caprylic oil phase, Tween 80 as an emulsifier, and PEG 200 as a co-emulsifier.…”
Section: Effect Of the Mcts On The Ddsmentioning
confidence: 99%
See 2 more Smart Citations
“…A drop of mixed micelle solution diluted to the appropriate concentration was placed on a copper grid covered with carbon film and negatively stained with phosphotungstic acid solution (2%, w v −1 ) for 30 s [34]. The morphology was observed by TEM after drying at room temperature.…”
Section: Transmission-electron Microscopy (Tem) Analysis Of Vi-mmsmentioning
confidence: 99%